2018
DOI: 10.1080/13880209.2018.1476559
|View full text |Cite
|
Sign up to set email alerts
|

Antitubercular evaluation of root extract and isolated phytochemicals from Lophira lanceolata against two resistant strains of Mycobacterium tuberculosis

Abstract: Context: The roots of Lophira lanceolata Van Tiegh. Ex Keay (Ochnaceae) have numerous medicinal values in the Central African region. Even though the MeOH extract of the roots has shown antimycobacterial activities, the constituents responsible for this inhibitory activity remain unknown.Objective: Phytochemical investigation of the MeOH root extract of L. lanceolata and determination of the antimycobacterial activities of that extract and constituents against the growth of Mycobacterium tuberculosis.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Researchers have isolated several such compounds and demonstrated their activities against mycobacteria, including M. tuberculosis (Baldin et al 2018;Chaipukdee et al 2016;Jimenez-Arellanes et al 2013;Jyoti et al 2016;Kanokmedhakul et al 2012;Molina-Salinas et al 2006;Naik et al 2014;Nkot et al 2018). However, antimycobacterial activities of secondary metabolites against M. abscessus have rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have isolated several such compounds and demonstrated their activities against mycobacteria, including M. tuberculosis (Baldin et al 2018;Chaipukdee et al 2016;Jimenez-Arellanes et al 2013;Jyoti et al 2016;Kanokmedhakul et al 2012;Molina-Salinas et al 2006;Naik et al 2014;Nkot et al 2018). However, antimycobacterial activities of secondary metabolites against M. abscessus have rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Plants are a source of bioactive compounds that can treat various diseases (Rios & Recio 2005). Several research teams have reported anti-Mycobacterium tuberculosis activity of extracts from Tetradenia riparia (Baldin et al 2018), Persea americana (Jimenez-Arellanes et al 2013), Lophira lanceolata (Nkot et al 2018) and Flourensia cernua (Molina-Salinas et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have isolated several such compounds and demonstrated their activities against mycobacteria, including M. tuberculosis ( Baldin et al, 2018 ; Chaipukdee et al, 2016 ; Jimenez-Arellanes et al, 2013 ; Jyoti et al, 2016 ; Kanokmedhakul et al, 2012 ; Molina-Salinas et al, 2006 ; Naik et al, 2014 ; Nkot et al, 2018 ). However, antimycobacterial activities of secondary metabolites against M. abscessus have rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Plants are a source of bioactive compounds that can treat various diseases ( Rios & Recio, 2005 ). Several research teams have reported anti- Mycobacterium tuberculosis activity of extracts from Tetradenia riparia ( Baldin et al, 2018 ), Persea americana ( Jimenez-Arellanes et al, 2013 ), Lophira lanceolata ( Nkot et al, 2018 ) and Flourensia cernua ( Molina-Salinas et al, 2006 ). Northeastern Thailand has high plant diversity, which remains locally important as a source of traditional medicines ( Kaewpiboon et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 L. lanceolata is used for the treatment of toothache, liver infections, female sterility, cough, fever, heart pains, blood spitting, intercostals pain, stomach pain, dysmenorrhea, respiratory troubles, and to relieve the gripping of dysentery. 3 In Nigeria, it is used in the management of jaundice, measles and liver injury. 4,5 Traditional knowledge of indigenous communities about plant diversity makes them major contributors to primary health care for majority of the world population.…”
mentioning
confidence: 99%